PROFANITY LANGUAGE IN MEGAN THEE STALLION’S SONG LYRICS - Elsa Gustryansar; Muarifuddin Muarifuddin (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
This research aimed to analyze the types and the function of profanity language in Megan Thee Stallion‟s song lyrics; Thot Shit, Savage, and Hot Girl Summer. This research uses two theories, to analyze for types using the theory of Andersson and Trudgill (1990) and function using the theory of Pinker (2007). The data was collected through listening the song while reading the lyrics as whole part, identifying the profanity language to the song, taking notes from the lyrics that show of profanity language in Thot Shit, Savage, and Hot girl Summer song, identifying and classifying. This research is analyzed by presenting the data that contain of profanity language in Thot Shit, Savage, and Hot Girl Summer song lyrics, describing the context of situation of the data, interpreting the data based on the types and function of profanity language in Megan Thee Stallion’s song lyrics. The result of this research shows that the types of profanity language the researcher found namely expletive profanity, abusive profanity, humorous profanity, and auxiliary profanity. Meanwhile, the function the profanity language on the song’s lyrics are to express anger through abusive, dysphemistic, cathartic, and emphatic functions.